Penerapan Prinsip Customer Due Diligence Dalam Mencegah Tindak Pencucian Uang Di Pt Bank Artha Graha Internasional Cabang Batam - Lendrawati Lendrawati; Maninda Ayuwandari (Journal of Judicial Review, 2018)
This research aims to find about the application of Customer Due Diligence (CDD) based on Bank Indonesia Regulation Number 14/27/PBI/2012 on the Implementation of the Anti-Money Laundering and Terrorism Funding Preventation for Public Banks in preventing acts of money laundering in PT. Bank Artha Graha Internasional Branch of Batam. This research uses research methods which constitute the normative conceptual legal research about application of Customer Due Diligence and follow up on prevention of money laundering. This research was compiled by using the juridical normative research type. The source of the data used are secondary data sources. After the data is collected, researcher processed and analyzes the data. So collect lageal materials, and describing in connected in such a way, then drawn the conclusion that answers the problems that have been formulated. Based on the research results and conclusions generated discussion, based on the PBI 14/27/PBI/2012, Customer Due Diligence is an activity form of identification, verification, and monitoring is done to ensure the the transactions are in accordance with the customer’s profile, which in its application is a process sustainability, which began at the opening of the account and its performed continuously during the customer has accounts in PT. Bank Artha Graha Internasional Brach of Batam. Then when the discovery of a suspicious financial transactions, the PT. Bank Artha Graha Internasional Brach of Batam has the obligation to report suspicious financial transactions to the PT. Bank Artha Graha Internasional Center for acted upon. Next, reported suspicious transactions to PPATK